Positive electrode material and preparation method thereof, positive plate and sodium ion battery
Through the combination of Co2+ and Cu2+ dual-element doping and metal oxide and carbon coating, the problem of insufficient conductivity of the positive electrode material of sodium ion battery is solved, the structural stability and electrochemical performance of sodium ion battery are improved, and the battery is extended life.
Patent Information
- Application Number
- CN202411025553.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2024-12-13
AI Technical Summary
The structural stability and cycle life of sodium ion batteries are lower than that of lithium ion batteries, and the low conductivity of existing positive electrode materials limits its electrochemical performance, especially the insufficient conductivity of Na3V2 (PO4)3 materials, which affects its sodium Applications in ionic batteries.
Through dual element doping of Co2+ and Cu2+, lattice distortion is formed, the ion transport channel is broadened, and combined with the use of metal oxides and carbon cladding, the conductivity and structural stability of the material are enhanced, and Na3+x+yV2-x- yCoxCuy(PO4)3 positive electrode material.
It significantly reduces the diffusion resistance of Na+, improves diffusion kinetics, enhances the conductivity and cycling stability of the material, extends the battery life, and improves the electrochemical performance of sodium ion batteries.
Smart Images

Figure CN119133437A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to positive electrode materials and preparation methods thereof, positive electrode sheets and sodium ion batteries. Background Art
[0002] In recent years, sodium-ion batteries (SIBs) have attracted much attention due to their abundant sodium resources in nature and low cost. In addition, SIBs and LIBs (lithium-ion batteries) have similar electrochemical mechanisms, so the study of cheaper SIBs is of great significance to meet the development of large-scale energy storage. It should be noted that due to the large radius of sodium ions (rNa + =0.097nm, rLi + =0.068nm) and Na + Due to the huge volume change during the deintercalation from the electrode material, the structural stability and cycle life of SIBs are generally lower than those of LIBs. Therefore, it is crucial to develop cathode materials with three-dimensional channels and stable skeletons to achieve fast and stable transport of sodium ions, which is crucial to improve the electrochemical performance and kinetic characteristics of SIBs.
[0003] Currently, many sodium-ion cathode materials are widely studied. Among them, Na3V2(PO4)3 (NVP) with a NASICON structure has the advantages of high operating voltage, high specific capacity, high structural stability, etc. due to the "inductive effect" of the polyanion group. Therefore, this type of phosphate material is a very promising sodium-ion battery electrode material. However, the low conductivity of NVP seriously affects its electrochemical performance, thus limiting the application of this material. Therefore, carbon coating, particle size reduction and cation doping are usually used to improve the electrochemical performance of NVP materials.
[0004] In addition to meeting the requirements of isolating the positive electrode material from the electrolyte, inhibiting interfacial side reactions, inhibiting transition metal dissolution, inhibiting gas production, and improving the structure, the ideal coating strategy also needs to consider the ionic conductivity and electronic conductivity of the coating layer, as well as the compatibility with the electrolyte. The carbon coating can greatly improve the conductivity of the material, enhance the rate performance of the material, and enhance the depth of charge and discharge to reduce polarization. However, the carbon coating is unstable and is prone to fragmentation during long cycles due to the expansion and contraction of the NVP inside the bulk phase, thereby accelerating the failure and aging behavior of the material. Metal oxide coating has the advantages of low cost, easy operation, and significant effect. Thin layer coating has no significant effect on electronic conductivity and ionic conductivity, so it is widely used in actual production. However, in high-voltage systems, high-voltage resistant oxide coating is required to maintain stable operation.
[0005] The cation doping strategy can broaden the ion transport channel and stabilize the unit cell structure, thereby significantly improving the ionic conductivity and structural stability of the material. Currently, in practical applications, single-element doping is usually used, and there are no reports on dual-element doping strategies. Summary of the invention
[0006] In view of this, the present invention provides a positive electrode material and a preparation method thereof, a positive electrode sheet and a sodium ion battery. 2+ , Cu 2+ After double element doping, the material can form lattice distortion, broaden the ion transmission channel, and make Na + Diffusion resistance inside the material is reduced, increasing diffusion kinetics.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] In a first aspect, the present invention provides a positive electrode material, the positive electrode material comprising:
[0009] a) Matrix material, the chemical formula of the matrix material is Na 3+x+y V 2-x-y Co x Cu y (PO4)3, where 0.01≤x≤0.12, 0.01≤y≤0.12, and 0.02≤x+y≤0.2;
[0010] b) metal oxide, the metal oxide is anchored to a portion of the surface of the matrix material;
[0011] c) A carbon coating layer, which is disposed on at least a portion of the surface of the base material anchored with the metal oxide.
[0012] Preferably, the metal oxide includes at least one of lanthanum oxide (La2O3), tin oxide (SnO2), samarium oxide (Sm2O3), aluminum oxide (Al2O3), and zirconium oxide (ZrO2).
[0013] Preferably, the metal oxide is lanthanum oxide.
[0014] Preferably, the particle size D of the metal oxide is 50 It is 20~100nm.
[0015] Preferably, the mass ratio of metal oxide to matrix material is (0.1-2):100.
[0016] Preferably, the contact area between the metal oxide and the matrix material is denoted as S1, the surface area of the matrix material is denoted as S2, and the ratio of S1 / S2 is 1:(3-6).
[0017] Preferably, the carbon coating layer comprises nitrogen-doped carbon material.
[0018] Preferably, the thickness of the carbon coating layer is denoted as T, and the diameter of the substrate material is D 50 Denoted as D, the ratio of T / D is 1:(10~100).
[0019] In a second aspect, the present invention provides a method for preparing the above-mentioned positive electrode material, comprising the following steps:
[0020] S1, mixing a vanadium source, a reducing agent and water, and performing a first heating treatment to obtain a solution A;
[0021] S2, mixing solution A, a cobalt source, a copper source, a sodium source and a phosphate precursor, and subjecting the mixture to a second heating treatment to obtain a gel B;
[0022] S3, drying the gel B, preheating and grinding the obtained dry product to obtain an intermediate product;
[0023] S4, subjecting the intermediate product to a first high-temperature treatment in an inert gas atmosphere to obtain a matrix material;
[0024] S5, mixing the matrix material, the metal oxide, the nitrogen source, the carbon source and anhydrous ethanol to obtain a solution C;
[0025] S6, subjecting solution C to a third heating treatment to obtain a solid product;
[0026] S7, in an inert gas atmosphere, subjecting the solid product to a second high-temperature treatment, and then to a high-temperature ball milling treatment to obtain a positive electrode material.
[0027] In the embodiment of the present invention, the vanadium source includes vanadium trioxide (V2O3), vanadium dioxide (VO2), vanadium pentoxide (V2O5), ammonium metavanadate (NH4VO3), peroxyvanadic acid (H4V2O 10 ), at least one of vanadium hydroxide (V(OH)3), sodium vanadate (Na3VO4), and sodium metavanadate (Na4V2O7).
[0028] In an embodiment of the present invention, the reducing agent includes at least one of citric acid, glucose and sucrose.
[0029] In an embodiment of the present invention, the cobalt source includes at least one of cobalt oxalate, cobalt nitrate, cobalt chloride, cobalt sulfate, cobalt oxide, and cobalt hydroxide.
[0030] In an embodiment of the present invention, the copper source includes at least one of copper oxalate, copper chloride, copper nitrate, copper sulfate, copper bromide, copper oxide, copper hydroxide, copper cyanide, and fatty acid copper.
[0031] In an embodiment of the invention, the sodium source comprises sodium hydroxide.
[0032] In an embodiment of the present invention, the phosphate precursor includes at least one of diammonium phosphate (NH4H2PO4), diammonium hydrogen phosphate ((NH4)2HPO4), and ammonium phosphate ((NH4)3PO4).
[0033] In an embodiment of the present invention, the nitrogen source includes at least one of urea, ethylenediamine, melamine, acetonitrile and phenbutylamine.
[0034] In an embodiment of the present invention, the carbon source includes at least one of glucose, asphalt, polydopamine, resorcinol, formaldehyde, starch, sucrose, sodium carboxymethyl cellulose, polyvinylidene fluoride, polyvinyl pyrrolidone, tannic acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, anthracene or aniline.
[0035] Preferably, the mass ratio of the vanadium source, the reducing agent and water is 1:(2-5):(5-50).
[0036] Preferably, the molar ratio of the vanadium source to the cobalt source is (20-200):1.
[0037] Preferably, the molar ratio of the vanadium source to the copper source is (20-200):1.
[0038] Preferably, the molar ratio of the vanadium source to the sodium source is (1-4):1.
[0039] Preferably, the molar ratio of the vanadium source to the phosphate precursor is (0.5-5):1.
[0040] Preferably, the mass ratio of the matrix material, the metal oxide, the nitrogen source and the carbon source is 100:(0.1-2):(0.1-2):(0.1-2).
[0041] Preferably, in step S1, the temperature of the first heating treatment is 60-100° C., and the time of the first heating treatment is 20-60 min.
[0042] Preferably, in step S2, the temperature of the second heat treatment is 60-100°C.
[0043] Preferably, in step S3, the drying temperature is 60-100° C., and the drying time is 10-15 hours.
[0044] Preferably, in step S3, the temperature of the preheating treatment is 300-550° C., and the time of the preheating treatment is 2-6 hours.
[0045] Preferably, in step S3, the grinding rate is 50-150 rpm / min, and the grinding time is 30-90 min.
[0046] Preferably, in step S4, the temperature of the first high temperature treatment is 600-1000° C., and the time of the first high temperature treatment is 1-10 hours.
[0047] Preferably, in step S6, the temperature of the third heat treatment is 60-120°C.
[0048] Preferably, in step S7, the temperature of the second high temperature treatment is 700-900° C., and the time of the second high temperature treatment is 1-12 hours.
[0049] Preferably, in step S7, the temperature of the high-temperature ball milling treatment is 600-900° C., the speed of the high-temperature ball milling treatment is 50-150 rpm / min, and the time of the high-temperature ball milling treatment is 30-90 min.
[0050] In a third aspect, the present invention provides a positive electrode sheet, which includes the above-mentioned positive electrode material, or the positive electrode material prepared by the above-mentioned preparation method.
[0051] In a fourth aspect, the present invention provides a sodium ion battery comprising the above-mentioned positive electrode sheet.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] (1) One of the main reasons why sodium-ion batteries are inferior to lithium-ion batteries in terms of charge and discharge power is that Na + The radius is larger, and the diffusion resistance is greater after becoming a solvated sodium ion in the electrolyte. After entering the bulk phase of the positive electrode material, the solid phase diffusion speed between the bulk phases of the material is too slow. The means generally adopted for this is to reduce the particle size of the material and reduce the diffusion distance of the sodium ions. However, the sodium ion battery has a low specific energy. The positive electrode material with a small particle size is not easy to make a high compaction density electrode. The Co with a smaller ion radius is used between the crystal lattices of the material Na3V2(PO4)3. 2+ , Cu 2+ Replacement Part V 4+ , because Co 2+ , Cu 2+ 、V 4+ The number of electron shells is the same, but Co 2+ , Cu 2+ The number of protons inside the nucleus is larger, and the inventors were surprised to find that Cu 2+ Compared with single element doping, the Co 2+ , Cu 2+ After double element doping, the material can form lattice distortion, broaden the ion transmission channel, and make Na + The diffusion resistance inside the material is reduced, the diffusion kinetics are increased, and the DC internal resistance DCR is significantly reduced.
[0054] (2) The capacity of the positive electrode material of sodium ion batteries is much lower than that of hard carbon negative electrode materials, which is the difficulty that limits the long-range requirements of sodium ion batteries for electric vehicles. Na3V2(PO4)3 is used as a positive electrode material for sodium ion batteries. 1 mol of the compound contains 3 mol of Na + , using the divalent ion Co 2+ , Cu 2+ Atom doping of the bulk phase of the material to replace V 4+ , the same molecular weight of Na needs to be supplemented + To maintain charge balance to form Na 3+x+y V 2-x-y Co x Cu y (PO4)3, thereby increasing the capacity, improving the first coulombic efficiency and capacity retention rate.
[0055] (3) Bulk coating of positive electrode materials is the most common method to improve the performance of positive electrode materials. However, when carbon is coated on the surface of the positive electrode material, the carbon layer is easily detached from the surface of the positive electrode material during the cycle, leaking the internal positive electrode material, reducing the conductivity of the material and causing direct contact between the electrolyte and the material, resulting in electrolyte failure, which in turn leads to further accelerated cell failure. Metal oxide coating has the advantages of low cost and simple technology. At the same time, metal oxide is riveted to the positive electrode material and then coated with carbon. The raised metal oxide helps to effectively combine the carbon material with the bulk phase, enhancing the stability of the carbon layer. The metal oxide has a higher dielectric constant and can be used with the positive electrode material Na with lattice distortion. 3+x+y V 2-x- y Co x Cu y (PO4)3 was treated with high temperature and high temperature ball milling, Na 3+x+y V 2-x-y Co x Cu y Due to atomic diffusion between (PO4)3 and metal oxides (such as La2O3), the metal oxides and the positive electrode materials are riveted together (atoms diffuse with each other under high-temperature ball milling, forming a doping-like effect on the surface of the material, which can make the two materials firmly contact each other). This structure can help the metal oxide form a "mortise and tenon-like" structure with the outermost carbon layer, making the contact between the carbon layer and the material more stable and not easy to fall off during high-voltage and long cycles, reducing electrolyte failure caused by direct contact between the material surface and the electrolyte, reducing polarization of the electrode material, and increasing the conductivity of the material while increasing cycle stability and conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 It is the SEM picture of the positive electrode material of the embodiment and the comparative example; Among them,
[0057] (a) is the positive electrode material (Na2O3) obtained in step (1) of comparative example 1 without coating of lanthanum oxide and carbon layer. 3.025 V 1.975 Co 0.0125 Cu 0.0125 SEM image of (PO4)3),
[0058] (b) is the positive electrode material (Na2O3) coated with lanthanum oxide obtained in step (2) of comparative example 1. 3.025 V 1.975 Co 0.0125 Cu 0.0125 SEM image of (PO4)3@La2O3),
[0059] (c) is the positive electrode material (Na 3.025 V 1.975 Co 0.0125 Cu 0.0125 SEM image of (PO4)3@La2O3 / C);
[0060] Figure 2 Comparison of discharge capacity of the batteries corresponding to the embodiment and the comparative example after 500 cycles;
[0061] Figure 3 It is a schematic diagram of the structure of the positive electrode material of the present invention, wherein 10 indicates a matrix material, 20 indicates a metal oxide, 30 indicates a carbon coating layer, 11 indicates an anchoring region, and 12 indicates a non-anchoring region. DETAILED DESCRIPTION
[0062] The present invention discloses positive electrode materials and methods for preparing the same, positive electrode sheets and sodium ion batteries. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve the same. It should be noted in particular that all similar substitutions and modifications are obvious to those skilled in the art and are deemed to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0063] In the description of the present invention, it should be noted that the terms "first", "second", etc. are only used for descriptive purposes, and do not indicate or imply relative importance.
[0064] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0065] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0066] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0067] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0068] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0069] Specifically, the present invention adopts the following technical solutions:
[0070] In a first aspect, the present invention provides a positive electrode material, the positive electrode material comprising:
[0071] a) Matrix material, the chemical formula of the matrix material is Na 3+x+y V 2-x-y Co x Cu y (PO4)3, where 0.01≤x≤0.12, 0.01≤y≤0.12, and 0.02≤x+y≤0.2;
[0072] b) metal oxide, the metal oxide is anchored to a portion of the surface of the matrix material;
[0073] c) A carbon coating layer, which is disposed on at least a portion of the surface of the base material anchored with the metal oxide.
[0074] In the present invention, the positive electrode material has the following two improvements:
[0075] (1) Improvement of base material
[0076] The base material was Co 2+ and Cu 2+ Double element doping, because Co 2+ , Cu 2+ 、V 4+ The number of electron shells is the same, but Co 2+ , Cu 2+ The number of protons inside the nucleus is larger, and the inventors were surprised to find that Cu 2+ Compared with single element doping, the Co 2+ , Cu 2+ After double element doping, the material can form lattice distortion, broaden the ion transmission channel, and make Na + The diffusion resistance inside the material is reduced, the diffusion kinetics are increased, and the DC internal resistance DCR is significantly reduced.
[0077] At the same time, Na3V2(PO4)3 is used as the positive electrode material of sodium ion batteries. 1 mol of the compound contains 3 mol of Na + , using the divalent ion Co 2+ , Cu 2+ Atom doping of the bulk phase of the material to replace V 4+ , the same molecular weight of Na needs to be supplemented + To maintain charge balance to form Na 3+x+y V 2-x-y Co x Cu y (PO4)3, thereby increasing the capacity, improving the first coulombic efficiency and capacity retention rate.
[0078] (2) Improvement of the coating layer
[0079] The metal oxide coating has the advantages of low cost and simple technology. At the same time, the metal oxide is riveted to the positive electrode material and then carbon-coated. The raised metal oxide helps to effectively bond the carbon material with the bulk phase, enhance the stability of the carbon layer, make the contact between the carbon layer and the material more stable, and is not easy to fall off during high-voltage and long cycles. It reduces electrolyte failure caused by direct contact between the material surface and the electrolyte, reduces polarization of the electrode material, increases the conductivity of the material while increasing cycle stability and conductivity.
[0080] In the present invention, the metal oxide is anchored to part of the surface of the matrix material, which means that the metal oxide contacts part of the surface of the matrix material in the form of particles, and atoms diffuse mutually at the interface between the metal oxide and the matrix material, forming a quasi-doping effect, so that the two are in firm contact with each other.
[0081] In the present invention, the carbon coating layer is arranged on at least a portion of the surface of the matrix material anchored with the metal oxide, the surface of the matrix material anchored with the metal oxide includes an anchoring region of the metal oxide and a non-anchoring region where the metal oxide is not anchored, and the carbon coating layer and the matrix material include the following two contact modes: 1) in the non-anchoring region, the carbon coating layer is in direct contact with the surface of the matrix material; 2) in the anchoring region, the carbon coating layer is in indirect contact with the surface of the matrix material through the metal oxide.
[0082] Preferably, the metal oxide includes at least one of lanthanum oxide (La2O3), tin oxide (SnO2), samarium oxide (Sm2O3), aluminum oxide (Al2O3), and zirconium oxide (ZrO2).
[0083] Preferably, the metal oxide is lanthanum oxide. Lanthanum oxide has high oxidation potential, high thermal stability, a melting point of more than 2,000 degrees Celsius, and is inactive. Using it as a positive electrode coating can effectively improve the high-voltage stability of the material and prevent the electrolyte from oxidative decomposition. At the same time, with its high dielectric constant and electrophilic properties, it can attract organic solvents, achieve rapid wetting, and enhance liquid phase diffusion dynamics.
[0084] Preferably, the particle size D of the metal oxide is 50 For example, the particle size D of the metal oxide is 20 to 100 nm. 50 It is any value among 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, and 100nm, or any value within the range consisting of any two of the above values.
[0085] Preferably, the particle size D of the metal oxide is 50 It is 30 to 50 nm.
[0086] Preferably, the mass ratio of the metal oxide to the matrix material is (0.1-2): 100. Exemplarily, the mass ratio of the metal oxide to the matrix material is any value among 0.1:100, 0.2:100, 0.4:100, 0.5:100, 0.6:100, 0.8:100, 1:100, 1.2:100, 1.4:100, 1.5:100, 1.6:100, 1.8:100, 2:100 or any value within the range consisting of any two of the above values.
[0087] Preferably, the mass ratio of metal oxide to matrix material is (0.1-1):100. Metal oxide has good thermal stability and electrophilic properties, and as a coating material, it does not provide capacity. When the addition amount is too large, the material specific capacity will be reduced, and when the addition amount is too small, it cannot play the role of anchoring the surface carbon layer, quickly infiltrating the electrolyte, and the high-voltage stability of the material.
[0088] Preferably, the contact area between the metal oxide and the matrix material is recorded as S1 (i.e., the anchoring area of the metal oxide on the surface of the matrix material), the surface area of the matrix material is recorded as S2, and the ratio of S1 / S2 is 1:(3-6). Exemplarily, the ratio of S1 / S2 is any value among 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, or any value within the range of any two of the above values.
[0089] Preferably, the ratio of S1 / S2 is 1:(3-5).
[0090] Preferably, the carbon coating layer comprises nitrogen-doped carbon material. In the nitrogen-doped carbon material, nitrogen doping can improve its conductivity and adjust the pore size.
[0091] Preferably, the thickness of the carbon coating layer is denoted as T, and the diameter of the substrate material is D 50 Denoted as D, the ratio of T / D is 1:(10-100). Exemplarily, the ratio of T / D is any value among 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100 or any value within the range of any two of the above values. When the thickness of the carbon coating layer is too large, the specific capacity of the material will be reduced. When the thickness of the carbon coating layer is too thin, it cannot play the role of inhibiting the volume expansion of the material, and then it will break and fall off, losing the function of the coating carbon layer, increasing the polarization of the material, increasing the internal resistance, and reducing the cycle performance.
[0092] Preferably, the ratio of T / D is 1:(20-60).
[0093] In a second aspect, the present invention provides a method for preparing the above-mentioned positive electrode material, comprising the following steps:
[0094] S1, mixing a vanadium source, a reducing agent and water, and performing a first heating treatment to obtain a solution A;
[0095] S2, mixing solution A, a cobalt source, a copper source, a sodium source and a phosphate precursor, and subjecting the mixture to a second heating treatment to obtain a gel B;
[0096] S3, drying the gel B, preheating and grinding the obtained dry product to obtain an intermediate product;
[0097] S4, subjecting the intermediate product to a first high-temperature treatment in an inert gas atmosphere to obtain a matrix material;
[0098] S5, mixing the matrix material, the metal oxide, the nitrogen source, the carbon source and anhydrous ethanol to obtain a solution C;
[0099] S6, subjecting solution C to a third heating treatment to obtain a solid product;
[0100] S7, in an inert gas atmosphere, subjecting the solid product to a second high-temperature treatment, and then to a high-temperature ball milling treatment to obtain a positive electrode material.
[0101] In the embodiment of the present invention, the vanadium source includes vanadium trioxide (V2O3), vanadium dioxide (VO2), vanadium pentoxide (V2O5), ammonium metavanadate (NH4VO3), peroxyvanadic acid (H4V2O 10 ), at least one of vanadium hydroxide (V(OH)3), sodium vanadate (Na3VO4), and sodium metavanadate (Na4V2O7).
[0102] The reducing agent can reduce the redox valence of vanadium, which is beneficial to the synthesis of the matrix material. In an embodiment of the present invention, the reducing agent includes at least one of citric acid, glucose and sucrose.
[0103] In an embodiment of the present invention, the cobalt source includes at least one of cobalt oxalate, cobalt nitrate, cobalt chloride, cobalt sulfate, cobalt oxide, and cobalt hydroxide.
[0104] In an embodiment of the present invention, the copper source includes at least one of copper oxalate, copper chloride, copper nitrate, copper sulfate, copper bromide, copper oxide, copper hydroxide, copper cyanide, and fatty acid copper.
[0105] In an embodiment of the invention, the sodium source comprises sodium hydroxide.
[0106] In an embodiment of the present invention, the phosphate precursor includes at least one of diammonium phosphate (NH4H2PO4), diammonium hydrogen phosphate ((NH4)2HPO4), and ammonium phosphate ((NH4)3PO4).
[0107] In an embodiment of the present invention, the nitrogen source includes at least one of urea, ethylenediamine, melamine, acetonitrile, and phenylbutylamine. The nitrogen source exists in the form of small molecules, so it is easier to be doped into the precursor during the growth process, and exists in the precursor lattice in the form of atomic doping.
[0108] Preferably, the nitrogen source is urea.
[0109] In an embodiment of the present invention, the carbon source includes at least one of glucose, asphalt, polydopamine, resorcinol, formaldehyde, starch, sucrose, sodium carboxymethyl cellulose, polyvinylidene fluoride, polyvinyl pyrrolidone, tannic acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, anthracene or aniline.
[0110] Preferably, the mass ratio of the vanadium source, the reducing agent and the water is 1:(2-5):(5-50). Exemplarily, the mass ratio of the vanadium source, the reducing agent and the water is any value in 1:2:5, 1:2:50, 1:3:10, 1:4:20, 1:5:30, 1:5:40, 1:5:50 or any value in the range of any two of the above values.
[0111] Preferably, the molar ratio of the vanadium source to the cobalt source is (20-200): 1. Exemplarily, the molar ratio of the vanadium source to the cobalt source is any value among 20: 1, 40: 1, 60: 1, 80: 1, 100: 1, 120: 1, 140: 1, 160: 1, 180: 1, 200: 1, or any value within the range consisting of any two of the above values.
[0112] Preferably, the molar ratio of the vanadium source to the copper source is (20-200): 1. Exemplarily, the molar ratio of the vanadium source to the copper source is any value among 20: 1, 40: 1, 60: 1, 80: 1, 100: 1, 120: 1, 140: 1, 160: 1, 180: 1, 200: 1, or any value within the range consisting of any two of the above values.
[0113] Preferably, the molar ratio of the vanadium source to the sodium source is (1-4): 1. Exemplarily, the molar ratio of the vanadium source to the sodium source is any value among 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, or any value within the range consisting of any two of the above values.
[0114] Preferably, the molar ratio of the vanadium source to the phosphate precursor is (0.5-5): 1. Exemplarily, the molar ratio of the vanadium source to the phosphate precursor is any value among 0.5: 1, 0.6: 1, 0.7: 1, 0.8: 1, 0.9: 1, 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, or any value within the range consisting of any two of the above values.
[0115] Preferably, the mass ratio of the matrix material, the metal oxide, the nitrogen source and the carbon source is 100:(0.1-2):(0.1-2):(0.1-2). Exemplarily, the mass ratio of the matrix material, the metal oxide, the nitrogen source and the carbon source is any value in 100:0.1:0.1:0.1, 100:0.5:0.5:0.5, 100:1:1:1, 100:2:2:2 or any value in the range of any two of the above values.
[0116] Preferably, in step S1, the temperature of the first heat treatment is 60-100°C, and the time of the first heat treatment is 20-60 min. Exemplarily, the temperature of the first heat treatment is any value among 60°C, 70°C, 80°C, 90°C, 100°C, or any value within the range of any two of the above values, and the time of the first heat treatment is any value among 20 min, 30 min, 40 min, 50 min, 60 min, or any value within the range of any two of the above values.
[0117] Preferably, in step S1, the first heating treatment is performed under stirring at a conventional speed, such as 100 to 1000 rpm.
[0118] Preferably, in step S2, the temperature of the second heat treatment is 60-100° C. Exemplarily, the temperature of the second heat treatment is any value among 60° C., 70° C., 80° C., 90° C., 100° C., or any value within a range consisting of any two of the above values.
[0119] Preferably, in step S2, the second heating treatment is performed under stirring at a conventional speed, such as 100 to 1000 rpm.
[0120] Preferably, in step S3, the drying temperature is 60-100°C, and the drying time is 10-15h. Exemplarily, the drying temperature is any value among 60°C, 70°C, 80°C, 90°C, 100°C, or any value within the range of any two of the above values, and the drying time is any value among 10h, 11h, 12h, 13h, 14h, 15h, or any value within the range of any two of the above values.
[0121] Preferably, in step S3, the temperature of the preheating treatment is 300-550°C, and the time of the preheating treatment is 2-6 hours. Exemplarily, the temperature of the preheating treatment is any value among 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, or any value within the range of any two of the above values, and the time of the preheating treatment is any value among 2h, 3h, 4h, 5h, 6h, or any value within the range of any two of the above values.
[0122] Preferably, in step S3, the grinding rate is 50-150 rpm / min, and the grinding time is 30-90 min. Exemplarily, the grinding rate is any value of 50 rpm / min, 70 rpm / min, 90 rpm / min, 100 rpm / min, 110 rpm / min, 130 rpm / min, 150 rpm / min, or any value within the range of any two of the above values, and the grinding time is any value of 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, or any value within the range of any two of the above values.
[0123] Preferably, in step S4, the temperature of the first high temperature treatment is 600-1000°C, and the time of the first high temperature treatment is 1-10 hours. Exemplarily, the temperature of the first high temperature treatment is any value in 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, or any value in the range of any two of the above values, and the time of the first high temperature treatment is any value in 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, or any value in the range of any two of the above values.
[0124] Preferably, in step S6, the temperature of the third heating treatment is 60-120° C. Exemplarily, the temperature of the third heating treatment is any value among 60° C., 70° C., 80° C., 90° C., 100° C., 110° C., 120° C. or any value within the range of any two of the above values, and the third heating treatment is performed until the ethanol is completely evaporated.
[0125] Preferably, in step S6, the third heating treatment is performed under stirring at a conventional speed, such as 100 to 1000 rpm.
[0126] In step S7 of the preparation method of the present invention, the solid product is subjected to a second high temperature treatment in an inert gas atmosphere, and then subjected to a high temperature ball milling treatment to obtain a positive electrode material. The solid product includes a matrix material (positive electrode material Na 3+x+y V2-x- y Co x Cu y (PO4)3), metal oxides, nitrogen sources and carbon sources. Among them, metal oxides have a higher dielectric constant and can react with the positive electrode material Na with lattice distortion. 3+x+y V 2-x-y Co x Cu y (PO4)3 was treated with high temperature and high temperature ball milling, Na 3+x+ y V 2-x-y Co x Cu y Due to atomic diffusion between (PO4)3 and metal oxides (such as La2O3), the metal oxides and the positive electrode materials are riveted together (atoms diffuse with each other under high-temperature ball milling, forming a doping-like effect on the surface of the material, which can make the two materials firmly contact each other). This structure can help the metal oxide form a "mortise and tenon-like" structure with the outermost carbon layer, making the contact between the carbon layer and the material more stable and not easy to fall off during high-voltage and long cycles, reducing electrolyte failure caused by direct contact between the material surface and the electrolyte, reducing polarization of the electrode material, and increasing the conductivity of the material while increasing cycle stability and conductivity.
[0127] Preferably, in step S7, the temperature of the second high temperature treatment is 700-900°C, and the time of the second high temperature treatment is 1-12 hours. Exemplarily, the temperature of the second high temperature treatment is any value among 700°C, 750°C, 800°C, 850°C, 900°C, or any value within the range of any two of the above values, and the time of the second high temperature treatment is any value among 1h, 2h, 4h, 6h, 8h, 10h, 12h, or any value within the range of any two of the above values.
[0128] Preferably, in step S7, the temperature of the high temperature ball milling treatment is 600-900°C, the rate of the high temperature ball milling treatment is 50-150rpm / min, and the time of the high temperature ball milling treatment is 30-90min. Exemplarily, the temperature of the high temperature ball milling treatment is any value in 600°C, 700°C, 800°C, 900°C or any value in the range of any two of the above values, the rate of the high temperature ball milling treatment is any value in 50rpm / min, 70rpm / min, 90rpm / min, 100rpm / min, 110rpm / min, 130rpm / min, 150rpm / min or any value in the range of any two of the above values, and the time of the high temperature ball milling treatment is any value in 30min, 40min, 50min, 60min, 70min, 80min, 90min or any value in the range of any two of the above values.
[0129] In a third aspect, the present invention provides a positive electrode sheet, which includes the above-mentioned positive electrode material, or the positive electrode material prepared by the above-mentioned preparation method.
[0130] In an embodiment of the present invention, the positive electrode active material layer of the positive electrode sheet includes the above-mentioned positive electrode material, a conductive agent, and a binder.
[0131] In the embodiment of the present invention, the mass percentage of each component in the positive electrode active material layer is: positive electrode material 80% to 99%, conductive agent 0.5% to 10%, and binder 0.5% to 10%.
[0132] In the embodiment of the present invention, the conductive agent includes but is not limited to at least one of conductive graphite, conductive carbon black (e.g., conductive carbon black SP), conductive carbon fiber, carbon nanotube or graphene. In addition to the several specific substances listed above, other types of conductive agents recognized by those skilled in the art are within the protection scope of the present invention.
[0133] In the embodiment of the present invention, the binder includes but is not limited to at least one of polyvinylidene fluoride (PVDF), styrene butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC), polyacrylate (LA), and polyacrylic acid binder (PAA). In addition to the several specific substances listed above, other types of binders recognized by those skilled in the art are within the scope of protection of the present invention.
[0134] The present application has no particular restrictions on the preparation method of the positive electrode sheet. Those skilled in the art can prepare the positive electrode sheet according to conventional preparation methods as long as the purpose of the present application can be achieved. Exemplarily, the preparation method of the positive electrode sheet includes: mixing the positive electrode material, the conductive agent, and the binder uniformly, adding a solvent to prepare a positive electrode slurry; coating the positive electrode slurry on the positive electrode collector, drying, and pressing to obtain a positive electrode sheet.
[0135] In a fourth aspect, the present invention provides a sodium ion battery comprising the above-mentioned positive electrode sheet.
[0136] In the embodiment of the present invention, the battery structure includes but is not limited to button batteries, soft-pack batteries, cylindrical batteries, etc.
[0137] The present application has no particular restrictions on the negative electrode sheet, separator, and electrolyte in the battery, and those skilled in the art can select them according to actual needs as long as the purpose of the present application can be achieved.
[0138] The reagents, instruments or materials used in the present invention can be obtained through commercial channels.
[0139] The present invention will be further described below in conjunction with embodiments:
[0140] Example 1
[0141] (1) Precursor Na 3.025 V 1.975 Co 0.0125 Cu 0.0125 Synthesis of (PO4)3:
[0142] First, take 2g NH4VO3, weigh citric acid according to the mass ratio of NH4VO3 to citric acid of 1:2, mix and dissolve in 50mL deionized water, and heat and stir at 80℃ for 30 minutes until a transparent blue solution appears. Then add (n (NH4VO3) :n (Co(CH3COO)2) ) molar ratio of 80 Co(CH3COO)2 and (n (NH4VO3) :n (Cu(CH3COO)2) ) molar ratio of 80 Cu(CH3COO)2 and (n (NH4VO3) :n (NaOH) ) NaOH with a molar ratio of 2 and (n (NH4VO3) :n (NH4H2PO4) ) with a molar ratio of 0.67 to NH4H2PO4, and continue to heat and stir at 80°C. After the solution evaporates to a gel state, it is placed in a forced air drying oven at 80°C for 12 hours. Then, the obtained powder is preheated at 350°C for 4 hours in an air atmosphere. After cooling to room temperature, the obtained precursor is carefully ground and then placed in an argon atmosphere at 750°C for 8 hours to obtain the final Na 3.025 V 1.975 Co 0.0125 Cu 0.0125 (PO4)3 positive electrode material.
[0143] (2)Na 3.025 V 1.975 Co0.0125 Cu 0.0125 Preparation of (PO4)3@La2O3 / C:
[0144] According to the semi-finished product Na 3.025 V 1.975 Co 0.0125 Cu 0.0125 La2O3 oxide powder, urea and glucose were weighed respectively, i.e., the coating concentration of each coating was 0.5wt%, and the La2O3 coated powder, urea and glucose were ultrasonically dispersed in anhydrous ethanol, and mechanically stirred at 400rpm for 20 minutes, then transferred to a 70℃ water bath, and the semi-finished product sample to be coated was added, and mechanical stirring was continued at 400rpm until the ethanol evaporated completely. After drying, it was transferred to a muffle furnace and annealed at 800℃ for 2 hours. The obtained sample was ball-milled in a ball mill at a ball milling rate of 100rpm and a ball milling time of 60min. The obtained sample was Na 3.025 V 1.975 Co 0.0125 Cu 0.0125 (PO4)3@La2O3 / C.
[0145] Example 2
[0146] The difference between this embodiment and embodiment 1 is that: (NH4VO3) :n (Co(CH3COO)2) ) molar ratio is 20, (n (NH4VO3) :n (Cu(CH3COO)2) ) molar ratio is 20, the coating concentrations of La2O3 oxide powder, urea and glucose are all 0.1wt%, and the high temperature annealing temperature is 900°C. The specific preparation method is as follows:
[0147] (1) Precursor Na 3.1 V 1.9 Co 0.05 Cu 0.05 Synthesis of (PO4)3:
[0148] First, take 2g NH4VO3, weigh citric acid according to the mass ratio of 1:2, mix and dissolve in 50mL deionized water, and heat and stir at 80℃ for 30 minutes until a transparent blue solution appears. Then add (n (NH4VO3) :n (Co(CH3COO)2) ) molar ratio of Co(CH3COO)2 to (n (NH4VO3) :n (Cu(CH3COO)2) ) molar ratio of Cu(CH3COO)2 to (n (NH4VO3) :n (NaOH) ) NaOH with a molar ratio of 2 and (n (NH4VO3) :n(NH4H2PO4) ) with a molar ratio of 0.67 to NH4H2PO4, and continue to heat and stir at 80°C. After the solution evaporates to a gel state, it is placed in a forced air drying oven at 80°C for 12 hours. Then, the obtained powder is preheated at 350°C for 4 hours in an air atmosphere. After cooling to room temperature, the obtained precursor is carefully ground and then placed in an argon atmosphere at 750°C for 8 hours to obtain the final Na 3.1 V 1.9 Co 0.05 Cu 0.05 (PO4)3 positive electrode material.
[0149] (2)Na 3.1 V 1.9 Co 0.05 Cu 0.05 Preparation of (PO4)3@La2O3 / C:
[0150] According to the semi-finished product Na 3.1 V 1.9 Co 0.05 Cu 0.05 La2O3 oxide powder, urea and glucose were weighed at 0.1% of the mass of the (PO4)3 sample, that is, the coating concentration of each coating was 0.1wt%. The La2O3 coated powder, urea and glucose were ultrasonically dispersed in anhydrous ethanol, and mechanically stirred at 400rpm for 20 minutes. Then, the mixture was transferred to a 70℃ water bath, and the semi-finished sample to be coated was added. The mechanical stirring was continued at 400rpm until the ethanol evaporated completely. After drying, the mixture was transferred to a muffle furnace and annealed at 900℃ for 2 hours. The obtained sample was ball milled in a ball mill at a ball milling rate of 100rpm and a ball milling time of 60min. The obtained sample was Na 3.1 V 1.9 Co 0.05 Cu 0.05 (PO4)3@La2O3 / C.
[0151] Example 3
[0152] The difference between this embodiment and embodiment 1 is that: (NH4VO3) :n (Co(CH3COO)2) ) molar ratio is 200, (n (NH4VO3) :n (Cu(CH3COO)2) ) molar ratio is 200, the coating concentrations of La2O3 oxide powder, urea and glucose are all 1.0wt%, and the high temperature annealing temperature is 700°C. The specific preparation method is as follows:
[0153] (1) Precursor Na 3.01 V 1.99 Co 0.005 Cu0.005 Synthesis of (PO4)3:
[0154] First, take 2g NH4VO3, weigh citric acid according to the mass ratio of 1:2, mix and dissolve in 50mL deionized water, and heat and stir at 80℃ for 30 minutes until a transparent blue solution appears. Then add (n (NH4VO3) :n (Co(CH3COO)2) ) molar ratio of Co(CH3COO)2 to (n (NH4VO3) :n (NH4VO3) :n (Co(CH3COO)2)(Cu(CH3COO)2) ) molar ratio of Cu(CH3COO)2 to (n (NH4VO3) :n (NaOH) ) NaOH with a molar ratio of 2 and (n (NH4VO3) :n (NH4H2PO4) ) with a molar ratio of 0.67 to NH4H2PO4, and continue to heat and stir at 80°C. After the solution evaporates to a gel state, it is placed in a forced air drying oven at 80°C for 12 hours. Then, the obtained powder is preheated at 350°C for 4 hours in an air atmosphere. After cooling to room temperature, the obtained precursor is carefully ground and then placed in an argon atmosphere at 750°C for 8 hours to obtain the final Na 3.01 V 1.99 Co 0.005 Cu 0.005 (PO4)3 positive electrode material.
[0155] (2)Na 3.01 V 1.99 Co 0.005 Cu 0.005 Preparation of (PO4)3@La2O3 / C:
[0156] According to the semi-finished product Na 3.01 V 1.99 Co 0.005 Cu 0.005 La2O3 oxide powder, urea and glucose were weighed, i.e., the coating concentration of each coating was 2.0wt%. La2O3 coated powder, urea and glucose were ultrasonically dispersed in anhydrous ethanol, and mechanically stirred at 400rpm for 20 minutes. Then, the mixture was transferred to a 70°C water bath, and the semi-finished sample to be coated was added. Mechanical stirring was continued at 400rpm until the ethanol was evaporated. After drying, the mixture was transferred to a muffle furnace and annealed at 700°C for 2 hours. The obtained sample was ball-milled in a ball mill at a ball milling rate of 100rpm and a ball milling time of 60min. The obtained sample was Na 3.01 V 1.99 Co 0.005 Cu0.005 (PO4)3@La2O3 / C.
[0157] Example 4
[0158] The difference between this embodiment and embodiment 1 is that: (NH4VO3) :n (Co(CH3COO)2) ) molar ratio is 20, (n (NH4VO3) :n (Cu(CH3COO)2) ) molar ratio is 200. The specific preparation method is as follows:
[0159] (1) Precursor Na 3.055 V 1.945 Co 0.05 Cu 0.005 Synthesis of (PO4)3:
[0160] First, take 2g NH4VO3, weigh citric acid according to the mass ratio of 1:2, mix and dissolve in 50mL deionized water, and heat and stir at 80℃ for 30 minutes until a transparent blue solution appears. Then add (n (NH4VO3) :n (Co(CH3COO)2) ) molar ratio of Co(CH3COO)2 to (n (NH4VO3) :n (Cu(CH3COO)2) ) molar ratio of Cu(CH3COO)2 to (n (NH4VO3) :n (NaOH) ) NaOH with a molar ratio of 2 and (n (NH4VO3) :n (NH4H2PO4) ) with a molar ratio of 0.67 to NH4H2PO4, and continue to heat and stir at 80°C. After the solution evaporates to a gel state, it is placed in a forced air drying oven at 80°C for 12 hours. Then, the obtained powder is preheated at 350°C for 4 hours in an air atmosphere. After cooling to room temperature, the obtained precursor is carefully ground and then placed in an argon atmosphere at 750°C for 8 hours to obtain the final Na 3.055 V 1.945 Co 0.05 Cu 0.005 (PO4)3 positive electrode material.
[0161] (2)Na 3.055 V 1.945 Co 0.05 Cu 0.005 Preparation of (PO4)3@La2O3 / C:
[0162] According to the semi-finished product Na 3.055 V 1.945 Co 0.05 Cu 0.005La2O3 oxide powder, urea and glucose were weighed to be 0.5% of the mass of the (PO4)3 sample, that is, the coating concentration of each coating was 0.5wt%, and the La2O3 coated powder, urea and glucose were ultrasonically dispersed in anhydrous ethanol, and mechanically stirred at 400rpm for 20 minutes, then transferred to a 70℃ water bath, and the semi-finished product sample to be coated was added, and mechanical stirring was continued at 400rpm until the ethanol evaporated completely. After drying, it was transferred to a muffle furnace and annealed at 800℃ for 2 hours. The obtained sample was ball-milled in a ball mill at a ball milling rate of 100rpm and a ball milling time of 60min. The obtained sample was Na 3.055 V 1.945 Co 0.05 Cu 0.005 (PO4)3@La2O3 / C.
[0163] Example 5
[0164] The difference between this embodiment and embodiment 1 is that: (NH4VO3) :n (Co(CH3COO)2) ) molar ratio is 200, (n (NH4VO3) :n (Cu(CH3COO)2) ) molar ratio is 20. The specific preparation method is as follows:
[0165] (1) Precursor Na 3.055 V 1.945 Co 0.005 Cu 0.05 Synthesis of (PO4)3:
[0166] First, take 2g NH4VO3, weigh citric acid according to the mass ratio of 1:2, mix and dissolve in 50mL deionized water, and heat and stir at 80℃ for 30 minutes until a transparent blue solution appears. Then add (n (NH4VO3) :n (Co(CH3COO)2) ) molar ratio of Co(CH3COO)2 to (n (NH4VO3) :n (Cu(CH3COO)2) ) molar ratio of Cu(CH3COO)2 to (n (NH4VO3) :n (NaOH) ) NaOH with a molar ratio of 2 and (n (NH4VO3) :n (NH4H2PO4) ) with a molar ratio of 0.67 to NH4H2PO4, and continue to heat and stir at 80°C. After the solution evaporates to a gel state, it is placed in a forced air drying oven at 80°C for 12 hours. Then, the obtained powder is preheated at 350°C for 4 hours in an air atmosphere. After cooling to room temperature, the obtained precursor is carefully ground and then placed in an argon atmosphere at 750°C for 8 hours to obtain the final Na 3.055 V1.945 Co 0.005 Cu 0.05 (PO4)3 positive electrode material.
[0167] (2)Na 3.055 V 1.945 Co 0.005 Cu 0.05 Preparation of (PO4)3@La2O3 / C:
[0168] According to the semi-finished product Na 3.055 V 1.945 Co 0.005 Cu 0.05 La2O3 oxide powder, urea and glucose were weighed to be 0.5% of the mass of the (PO4)3 sample, that is, the coating concentration of each coating was 0.5wt%, and the La2O3 coated powder, urea and glucose were ultrasonically dispersed in anhydrous ethanol, and mechanically stirred at 400rpm for 20 minutes, then transferred to a 70℃ water bath, and the semi-finished product sample to be coated was added, and mechanical stirring was continued at 400rpm until the ethanol evaporated completely. After drying, it was transferred to a muffle furnace and annealed at 800℃ for 2 hours. The obtained sample was ball-milled in a ball mill at a ball milling rate of 100rpm and a ball milling time of 60min. The obtained sample was Na 3.055 V 1.945 Co 0.005 Cu 0.05 (PO4)3@La2O3 / C.
[0169] Comparative Example 1 (without carbon coating)
[0170] The difference between this comparative example and Example 1 is that no carbon coating layer is provided. The specific preparation method is as follows:
[0171] (1) Precursor Na 3.025 V 1.975 Co 0.0125 Cu 0.0125 Synthesis of (PO4)3:
[0172] First, take 2g NH4VO3, weigh citric acid according to the mass ratio of 1:2, mix and dissolve in 50mL deionized water, and heat and stir at 80℃ for 30 minutes until a transparent blue solution appears. Then add (n (NH4VO3) :n (Co(CH3COO)2) ) molar ratio of 80 Co(CH3COO)2 and (n (NH4VO3) :n (Cu(CH3COO)2) ) molar ratio of 80 Cu(CH3COO)2 and (n (NH4VO3) :n (NaOH) ) NaOH with a molar ratio of 2 and (n(NH4VO3) :n (NH4H2PO4) ) with a molar ratio of 0.67 to NH4H2PO4, and continue to heat and stir at 80°C. After the solution evaporates to a gel state, it is placed in a forced air drying oven at 80°C for 12 hours. Then, the obtained powder is preheated at 350°C for 4 hours in an air atmosphere. After cooling to room temperature, the obtained precursor is carefully ground and then placed in an argon atmosphere at 750°C for 8 hours to obtain the final Na 3.025 V 1.975 Co 0.0125 Cu 0.0125 (PO4)3 positive electrode material.
[0173] (2)Na 3.025 V 1.975 Co 0.0125 Cu 0.0125 Preparation of (PO4)3@La2O3:
[0174] According to the semi-finished product Na 3.025 V 1.975 Co 0.0125 Cu 0.0125 La2O3 oxide powder was weighed at 0.5% of the mass of the (PO4)3 sample, that is, the coating concentration of the coating was 0.5wt%. The La2O3 coated powder was ultrasonically dispersed in anhydrous ethanol, and mechanically stirred at 400rpm for 20 minutes. Then, it was transferred to a 70°C water bath, and the semi-finished product sample to be coated was added. Mechanical stirring was continued at 400rpm until the ethanol evaporated completely. After drying, it was transferred to a muffle furnace and annealed at 800°C for 2 hours. The obtained sample was ball-milled in a ball mill at a ball milling rate of 100rpm and a ball milling time of 60min. The obtained sample was Na 3.025 V 1.975 Co 0.0125 Cu 0.0125 (PO4)3@La2O3.
[0175] Comparative Example 2 (without Co 2+ / Cu 2+ , lanthanum oxide and carbon coating)
[0176] The difference between this comparative example and Example 1 is that there is no Co and Cu doping in the positive electrode material, no lanthanum oxide is added, and no carbon coating layer is provided. The specific preparation method is as follows:
[0177] Precursor Na3V2(PO 4)3Synthesis: First, take 2g NH4VO3, weigh citric acid according to the mass ratio of NH4VO3 to citric acid of 1:2, mix and dissolve in 50mL deionized water, and heat and stir at 80℃ for 30 minutes until a transparent blue solution appears. Then add (n (NH4VO3) :n (NaOH) ) NaOH with a molar ratio of 2 and (n (NH4VO3) :n (NH4H2PO4) ) with a molar ratio of 0.67 to NH4H2PO4, and continue to heat and stir at 80°C. After the solution evaporates to a gel state, it is placed in a blast drying oven at 80°C for 12 hours. Then, the resulting powder is preheated at 350°C for 4 hours in an air atmosphere. After cooling to room temperature, the resulting precursor is carefully ground, and then placed in an argon atmosphere at 750°C for 8 hours to obtain the final Na3V2(PO4)3 positive electrode material.
[0178] Comparative Example 3 (Cu 2+ Single element doping)
[0179] The difference between this comparative example and Example 1 is that there is no Co in the positive electrode material. 2+ Doping, Cu 2+ The specific preparation method is as follows:
[0180] (1) Precursor Na 3.025 V 1.975 Cu 0.025 Synthesis of (PO4)3:
[0181] First, take 2g NH4VO3, weigh citric acid according to the mass ratio of 1:2, mix and dissolve in 50mL deionized water, and heat and stir at 80℃ for 30 minutes until a transparent blue solution appears. Then add (n (NH4VO3) :n (Cu(CH3COO)2) ) molar ratio of 40 Cu(CH3COO)2 and (n (NH4VO3) :n (NaOH) ) NaOH with a molar ratio of 2 and (n NH4VO3) :n (NH4H2PO4) ) with a molar ratio of 0.67 to NH4H2PO4, and continue to heat and stir at 80°C. After the solution evaporates to a gel state, it is placed in a forced air drying oven at 80°C for 12 hours. Then, the obtained powder is preheated at 350°C for 4 hours in an air atmosphere. After cooling to room temperature, the obtained precursor is carefully ground and then placed in an argon atmosphere at 750°C for 8 hours to obtain the final Na 3.025 V 1.975 Cu 0.025(PO4)3 positive electrode material.
[0182] (2)Na 3.025 V 1.975 Cu 0.025 Preparation of (PO4)3@La2O3 / C:
[0183] According to the semi-finished product Na 3.025 V 1.975 Cu 0.025 La2O3 oxide powder, urea and glucose were weighed to be 0.5% of the mass of the (PO4)3 sample, that is, the coating concentration of each coating was 0.5wt%, and the La2O3 coated powder, urea and glucose were ultrasonically dispersed in anhydrous ethanol, and mechanically stirred at 400rpm for 20 minutes, then transferred to a 70℃ water bath, and the semi-finished product sample to be coated was added, and mechanical stirring was continued at 400rpm until the ethanol evaporated completely. After drying, it was transferred to a muffle furnace and annealed at 800℃ for 2 hours. The obtained sample was ball-milled in a ball mill at a ball milling rate of 100rpm and a ball milling time of 60min. The obtained sample was Na 3.025 V 1.975 Cu 0.025 (PO4)3@La2O3 / C.
[0184] Comparative Example 4 (without La2O3)
[0185] The difference between this comparative example and Example 1 is that no lanthanum oxide is added to the positive electrode material. The specific preparation method is as follows:
[0186] (1) Precursor Na 3.025 V 1.975 Co 0.0125 Cu 0.0125 Synthesis of (PO4)3:
[0187] First, take 2g NH4VO3, weigh citric acid according to the mass ratio of NH4VO3 to citric acid of 1:2, mix and dissolve in 50mL deionized water, and heat and stir at 80℃ for 30 minutes until a transparent blue solution appears. Then add (n (NH4VO3) :n (Co(CH3COO)2) ) molar ratio of 80 Co(CH3COO)2 and (n (NH4VO3) :n (Cu(CH3COO)2) ) molar ratio of 80 Cu(CH3COO)2 and (n (NH4VO3) :n (NaOH) ) NaOH with a molar ratio of 2 and (n (NH4VO3) :n (NH4H2PO4)) with a molar ratio of 0.67 to NH4H2PO4, and continue to heat and stir at 80°C. After the solution evaporates to a gel state, it is placed in a forced air drying oven at 80°C for 12 hours. Then, the obtained powder is preheated at 350°C for 4 hours in an air atmosphere. After cooling to room temperature, the obtained precursor is carefully ground and then placed in an argon atmosphere at 750°C for 8 hours to obtain the final Na 3.025 V 1.975 Co 0.0125 Cu 0.0125 (PO4)3 positive electrode material.
[0188] (2)Na 3.025 V 1.975 Co 0.0125 Cu 0.0125 Preparation of (PO4)3@C:
[0189] According to the semi-finished product Na 3.025 V 1.975 Co 0.0125 Cu 0.0125 Urea and glucose were weighed to account for 0.5% of the mass of the (PO4)3 sample, that is, the coating concentration of each coating was 0.5wt%. Urea and glucose were ultrasonically dispersed in anhydrous ethanol together, and mechanically stirred at 400rpm for 20 minutes. Then, the sample was transferred to a 70°C water bath, and the semi-finished product sample to be coated was added. The mechanical stirring was continued at 400rpm until the ethanol evaporated completely. After drying, the sample was transferred to a muffle furnace and annealed at 800°C for 2 hours. The obtained sample was ball-milled in a ball mill at a ball milling rate of 100rpm and a ball milling time of 60min. The obtained sample was Na 3.025 V 1.975 Co 0.0125 Cu 0.0125 (PO4)3@C.
[0190] Morphological characterization
[0191] The positive electrode material prepared in step (1) of comparative example 1, the positive electrode material prepared in step (2) of comparative example 1, and the positive electrode material prepared in example 1 were observed using a scanning electron microscope (SEM).
[0192] pass Figure 1 From the SEM image, it can be seen that the surface of the positive electrode material precursor sample prepared in step (1) of comparative example 1 without oxide doping has no obvious protrusions ( Figure 1 As shown in a), after oxide doping and coating, oxide protrusions are distributed on the surface of the positive electrode material ( Figure 1As shown in b), the protrusions are riveted to each other by dipole-dipole action, which provides a high degree of stability for the carbon coating, so that the carbon layer can be stably attached to the material during the cycle. After carbon coating, the carbon layer is spread all over the surface of the positive electrode material ( Figure 1 As shown in c), the carbon layer is fixed with oxide particles and can be more stably attached to the surface of the material.
[0193] Battery preparation, test methods and conditions:
[0194] (1) Preparation of batteries:
[0195] A hard carbon material is used as the negative electrode active material, and it is mixed with a conductive agent (conductive carbon black SP) and a binder (polyvinylidene fluoride PVDF) in a mass ratio of 97:1.5:1.5, coated on an aluminum foil, and dried, pressed and other processes to form a negative electrode sheet. The size of the negative electrode sheet is (100mm×55mm). The positive electrode material prepared in the above embodiments and comparative examples is used as the positive electrode, and it is mixed with a conductive agent (conductive carbon black SP) and a binder (polyvinylidene fluoride PVDF) in a mass ratio of 97:1.5:1.5, coated on an aluminum foil, and the size of the positive electrode sheet is 96mm×51mm. Whatman glass fiber separator GF / D is used as a separator. The electrolyte is 1 mol / L NaClO4, and the solvent is a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1. For the full battery, the capacity ratio of the positive electrode to the negative electrode is 1.2, and the loading amount of the negative electrode is 9.8mg cm -2 . The assembly process adopts the soft pack lamination method. Lamination: The positive electrode sheet, glass fiber separator, and negative electrode sheet are stacked in order to obtain a battery cell. Assembly: The stacked battery cells are hot-pressed and placed in an aluminum-plastic film for top and side sealing. Injection: The electrolyte is injected into the battery. Packaging: The battery after injection is sealed, and the injection coefficient is 3g / Ah. Formation: The packaged battery is subjected to formation treatment. When comparing the electrochemical properties of different positive electrode sheets, the load capacity of the negative electrode remains basically the same. Set the charge and discharge cut-off voltage to 2.5-4.0V, the charge and discharge current to 1A / g, and end the test after 500 cycles.
[0196] (2) Test methods and conditions
[0197] 1) 500-cycle capacity retention rate test method:
[0198] ① After the capacity division is completed, the battery is first charged to 4.0V with a constant current of 1C, and then charged to I≤0.05C with a constant voltage of 4.0V;
[0199] ② After standing for 5 minutes, discharge the battery at a constant current of 1C to 2.5V to obtain the discharge capacity C1;
[0200] ③Let stand for 30 minutes.
[0201] ④ Repeat steps ①-③ 499 times to obtain the discharge capacity C500;
[0202] The 500-cycle capacity retention rate is calculated as (C500) / (C1)*100%.
[0203] 2) First coulombic efficiency test method:
[0204] After the battery is manufactured, it is first charged to 3.75V at a constant current of 0.1C to obtain the formation capacity C0. Then the battery is divided into different capacities, charged to 4.0V at a constant current of 0.33C, and then charged to I≤0.05C at a constant voltage of 4.0V to obtain the battery capacity C1 after the capacity division. After standing for 5 minutes, the battery is discharged to 2.5V at a constant current of 1C to obtain the discharge capacity C2, and then discharged to 2.5V at a constant current of 0.1C to obtain the discharge capacity C3, and discharged to 2.5V at a constant current of 0.01C to obtain the discharge capacity C4; the first coulomb efficiency (first efficiency) is calculated according to (C2+C3+C4) / (C0+C1)*100%.
[0205] 3) 50% SOC, 25℃, 2C, 10s DCR (DC internal resistance) test method
[0206] ①0.33C constant current and constant voltage charging to 4.0V;
[0207] ②Let stand for 30 minutes;
[0208] ③ 0.33C constant current discharge for 90 minutes, adjust the state of charge to 50% SOC;
[0209] ④Let stand for 30 minutes;
[0210] ⑤Discharge at 2C current for 10s and record the voltage before and after discharge.
[0211] DCR=(V 放电前 -V 放电末期 ) / Current
[0212] (3) Test results
[0213] Table 1
[0214]
[0215]
[0216] Note: S1 is the contact area of lanthanum oxide matrix material, S2 is the surface area of matrix material; T is the thickness of carbon coating layer, and D is the diameter of matrix material.
[0217] Table 2
[0218]
[0219] Through Table 2 and Figure 2 It can be seen that the first efficiency and capacity retention rate of Example 1 are the highest, indicating that the structural stability of the positive electrode material of Example 1 is the best.
[0220] In addition, the DC internal resistance test was conducted on the embodiments and comparative examples in Table 2. The DC internal resistance of Embodiment 1 was the lowest, indicating that the material has high electronic conductivity and ionic conductivity and low polarization.
[0221] Under the same doping amount, compared with the Cu in Comparative Example 3, 2+ Compared with single element doping, Example 1 is doped with Co 2+ , Cu 2+ After double element doping, the material can form lattice distortion, broaden the ion transmission channel, and make Na + The diffusion resistance inside the material is reduced, the diffusion kinetics are increased, and the DC internal resistance DCR is significantly reduced.
[0222] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A positive electrode material, characterized in that: The positive electrode material comprises: a) a matrix material, the chemical formula of which is Na 3+x+y V 2-x-y Co x Cu y (PO4)3, where 0.01≤x≤0.12, 0.01≤y≤0.12, and 0.02≤x+y≤0.2; b) a metal oxide, wherein the metal oxide is anchored to a portion of the surface of the base material; c) a carbon coating layer, wherein the carbon coating layer is disposed on at least a portion of the surface of the base material on which the metal oxide is anchored.
2. The positive electrode material according to claim 1, characterized in that The metal oxide includes at least one of lanthanum oxide, tin oxide, samarium oxide, aluminum oxide, and zirconium oxide; Preferably, the metal oxide is lanthanum oxide; Preferably, the particle size D of the metal oxide is 50 20~100nm; Preferably, the mass ratio of the metal oxide to the matrix material is (0.1-2):100; Preferably, the contact area between the metal oxide and the matrix material is denoted as S1, the surface area of the matrix material is denoted as S2, and the ratio of S1 / S2 is 1:(3-6).
3. The positive electrode material according to claim 1, characterized in that The carbon coating layer includes nitrogen-doped carbon material; Preferably, the thickness of the carbon coating layer is denoted as T, and the diameter of the base material is D 50 Denoted as D, the ratio of T / D is 1:(10~100).
4. The method for preparing the positive electrode material according to any one of claims 1 to 3, characterized in that: The steps include: S1, mixing a vanadium source, a reducing agent and water, and performing a first heating treatment to obtain a solution A; S2, mixing the solution A, the cobalt source, the copper source, the sodium source and the phosphate precursor, and subjecting the mixture to a second heating treatment to obtain a gel B; S3, drying the gel B, preheating and grinding the obtained dry product to obtain an intermediate product; S4, subjecting the intermediate product to a first high-temperature treatment in an inert gas atmosphere to obtain a matrix material; S5, mixing the matrix material, the metal oxide, the nitrogen source, the carbon source and anhydrous ethanol to obtain a solution C; S6, subjecting the solution C to a third heating treatment to obtain a solid product; S7, in an inert gas atmosphere, subjecting the solid product to a second high-temperature treatment, and then to a high-temperature ball milling treatment to obtain a positive electrode material.
5. The preparation method according to claim 4, characterized in that: The vanadium source includes at least one of vanadium trioxide, vanadium dioxide, vanadium pentoxide, ammonium metavanadate, peroxyvanadic acid, vanadium hydroxide, sodium vanadate, and sodium metavanadate; Preferably, the reducing agent comprises at least one of citric acid, glucose and sucrose; Preferably, the cobalt source includes at least one of cobalt oxalate, cobalt nitrate, cobalt chloride, cobalt sulfate, cobalt oxide, and cobalt hydroxide; Preferably, the copper source includes at least one of copper oxalate, copper chloride, copper nitrate, copper sulfate, copper bromide, copper oxide, copper hydroxide, copper cyanide, and fatty acid copper; Preferably, the sodium source comprises sodium hydroxide; Preferably, the phosphate precursor includes at least one of diammonium phosphate, diammonium hydrogen phosphate, and ammonium phosphate; Preferably, the nitrogen source includes at least one of urea, ethylenediamine, melamine, acetonitrile and phenbutylamine; Preferably, the carbon source includes at least one of glucose, asphalt, polydopamine, resorcinol, formaldehyde, starch, sucrose, sodium carboxymethyl cellulose, polyvinylidene fluoride, polyvinyl pyrrolidone, tannic acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, anthracene or aniline.
6. The preparation method according to claim 4, characterized in that: The mass ratio of the vanadium source, the reducing agent and the water is 1:(2-5):(5-50); Preferably, the molar ratio of the vanadium source to the cobalt source is (20-200):1; Preferably, the molar ratio of the vanadium source to the copper source is (20-200):1; Preferably, the molar ratio of the vanadium source to the sodium source is (1-4):1; Preferably, the molar ratio of the vanadium source to the phosphate precursor is (0.5-5):1; Preferably, the mass ratio of the matrix material, the metal oxide, the nitrogen source and the carbon source is 100:(0.1-2):(0.1-2):(0.1-2).
7. The preparation method according to claim 4, characterized in that: In step S1, the temperature of the first heating treatment is 60-100° C., and the time of the first heating treatment is 20-60 min; Preferably, in step S2, the temperature of the second heating treatment is 60-100°C; Preferably, in step S3, the temperature of the drying treatment is 60-100° C., and the time of the drying treatment is 10-15 hours; Preferably, in step S3, the temperature of the preheating treatment is 300-550° C., and the time of the preheating treatment is 2-6 hours; Preferably, in step S3, the grinding rate is 50-150 rpm / min, and the grinding time is 30-90 min; Preferably, in step S4, the temperature of the first high temperature treatment is 600-1000° C., and the time of the first high temperature treatment is 1-10 hours.
8. The preparation method according to claim 4, characterized in that: In step S6, the temperature of the third heating treatment is 60-120°C; Preferably, in step S7, the temperature of the second high temperature treatment is 700-900° C., and the time of the second high temperature treatment is 1-12 hours; Preferably, in step S7, the temperature of the high-temperature ball milling treatment is 600-900° C., the speed of the high-temperature ball milling treatment is 50-150 rpm / min, and the time of the high-temperature ball milling treatment is 30-90 min.
9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the positive electrode material described in any one of claims 1 to 3, or the positive electrode material prepared by the preparation method described in any one of claims 4 to 8.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode sheet according to claim 9.
Citation Information
Cited By
Lithium manganese iron phosphate positive electrode material, preparation method thereof and electrochemical device
CN121076126A
